PUSAT KEGIATAN MAHASISWA UNIVERSITAS TANJUNGPURA - Maulana, Muhammad Adji; Purnomo, Yudi; Pebriano, Valentinus (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2024)
Currently, the Student Activity Center (Pusgiwa) in Tanjungpura University faces both physical (structural) and non-physical (user habit) issues that makes the Pusgiwa area ineffective for student activities. The facilities are inadequate and misused. This final project aims to design a more adequate Student Activity Center for Untan students, incorporating an open concept while considering contextual aspects and the physical and non-physical issues experienced in the previous design. The design methodology employed is Richard Whitaker's eight-step design process, encompassing five steps in design and three post-design steps. Richard Whitaker's five design steps include initiation, definition, preparation, analysis, and synthesis. The three post-design steps consist of temporal evaluation, alternative solution evaluation, and final reevaluation. The outcome of the design is an open Pusgiwa area that fulfills the student